SIMULATION MODEL OF TROLLEY-BUS ROUTE (Perner's Contacts, 2008)
The article deals with the description of trolley-bus route simulation model, which was created in the simulation program Extend v.4. The model was created for the needs of transport system characteristics verification and its behaviour observation in dependence on the change of input values.
Keywords: simulation; model; transport